Morbidity and oncological outcomes of rectal cancer impaired by previous prostate malignancy. Issue 8 (10th May 2019) - Lakkis, Z; Vernerey, D; Mege, D; Faucheron, J-L; Panis, Y; Tuech, J-J; Lefevre, J H; Brouquet, A; Dumont, F; Borg, C; Woronoff, A-S; Meurisse, A; et al.
Abstract: Background: Specific surgical and oncological outcomes in patients with rectal cancer surgery after a previous diagnosis of prostate cancer have not been well described. The aim of this study was to compare surgical outcomes in patients with rectal cancer with or without a history of prostate cancer. Methods: Patients who had surgery for rectal cancer with (PC group) or without (no-PC group) previous curative treatment for prostate cancer were enrolled between January 2001 and December 2015. Comparisons between the two groups were performed by multivariable Cox analysis, and after propensity score matching in a 3 : 1 ratio for demographic and tumour characteristics, and surgical and oncological outcomes. Results: A total of 944 patients with rectal cancer were enrolled, of whom 10·8 per cent had a history of prostate cancer. After matching, 83 patients who had received treatment for prostate cancer were compared with 249 who had not. The PC and no-PC groups were similar regarding patient characteristics. Extended total mesorectal excision, conversion to open surgery, transfusion and tumour perforation were more frequent in the PC group than in the no-PC group. Major surgical morbidity (28 versus 17·2 per cent; P =  0·036), anastomotic leakage (25 versus 13·7 per cent; P =  0·019) and permanent stoma (41 versus 12·4 per cent; P < 0·001) occurred more frequently in the PC group. Local recurrence was increased significantly in the PC group (17 versus 8·0 per cent; P =  0·019), and resulted in a significant decrease in disease-free and overall survival. Conclusion: Prostate cancer treatment increases short- and long-term surgical morbidity in patients with rectal cancer, and impairs oncological outcomes. Graphical Abstract: The present study showed that a past history of prostate radiotherapy or prostatectomy for prostate cancer increased the risk of anastomotic leakage, permanent stoma after rectal resection and shorter survival. Morbity and outcomes worse